Pengaruh Citra Merek, Harga, Purna Jual, Dan Kualitas Produk Terhadap Keputusan Pembelian Sepeda Motor Yamaha Nmax (Studi Kasus pada Pembeli Sepeda Motor Yamaha Nmax di Dealer Yamaha Waja Gunung Agung) - Susanto Adi; Mulyadi Made (Jurnal Ilmiah Manajemen & Bisnis, 2017)
ABSTRACT The level of competition in the Indonesian automotive companies are very strict.Indonesia is a potential market for automotive companies, especially motorcycles.In addition, consumers also have different considerations and perceptions of the brand image, pricing, sales, and quality of products before making a purchase decision.The purpose of this study was to determine the impact of variable Brand Image, Price, After Sales, and Product Quality to Buying Decision Motorcycles Yamaha Nmax (Case Study on Yamaha Nmax Buyer in Yamaha Waja Gunung Agung Dealership). The analytical method used in this research is multiple linear analysis to determine the impact of variable Brand Image, Price, After Sales, and Product Quality to the BuyingDecision.The results of this study show variable Brand Image, Price, After Sales, and Product Quality, has a partial effect and significantly by 74.6% to the buying decision.